2(5c-1)-5=(8c+5)

Simple and best practice solution for 2(5c-1)-5=(8c+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5c-1)-5=(8c+5) equation:


Simplifying
2(5c + -1) + -5 = (8c + 5)

Reorder the terms:
2(-1 + 5c) + -5 = (8c + 5)
(-1 * 2 + 5c * 2) + -5 = (8c + 5)
(-2 + 10c) + -5 = (8c + 5)

Reorder the terms:
-2 + -5 + 10c = (8c + 5)

Combine like terms: -2 + -5 = -7
-7 + 10c = (8c + 5)

Reorder the terms:
-7 + 10c = (5 + 8c)

Remove parenthesis around (5 + 8c)
-7 + 10c = 5 + 8c

Solving
-7 + 10c = 5 + 8c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-8c' to each side of the equation.
-7 + 10c + -8c = 5 + 8c + -8c

Combine like terms: 10c + -8c = 2c
-7 + 2c = 5 + 8c + -8c

Combine like terms: 8c + -8c = 0
-7 + 2c = 5 + 0
-7 + 2c = 5

Add '7' to each side of the equation.
-7 + 7 + 2c = 5 + 7

Combine like terms: -7 + 7 = 0
0 + 2c = 5 + 7
2c = 5 + 7

Combine like terms: 5 + 7 = 12
2c = 12

Divide each side by '2'.
c = 6

Simplifying
c = 6

See similar equations:

| 4-1/2d=10 | | 3x+2x=5+3x | | N+2n=30 | | 6x+4x=74 | | 4.0=8.4/X | | 6(a-6)=48 | | a^3x-9ax^3=0 | | (p-6)(p-7)=0 | | 3x+2x=5+3 | | 3(d-4)=15 | | 8=4c-4 | | 4x+7,x=6 | | 6r+6=21r+9 | | y=2140x-53500 | | 47=11+12W | | 3/4+10=190 | | 8y+5x-3y+7-2x= | | 2x-5=4x-1+5 | | log[9]x=log[9]5+log[9]6-log[9]3 | | -5(1+2w)=20 | | 4x-16+6=2x+-6+2x | | 2-4x=-62 | | 1/2x-5+2x+2=10 | | -5(-1+k)=25 | | 7x+21=x/7 | | (d+1)=64 | | 3y+6y+8y= | | 2/3*2*-8= | | -4x+9x=-50 | | x^3+15x^2+72x+108=0 | | 4y-10=6+y | | 2x^2+25x+48=0 |

Equations solver categories